Double Tragedy for Women with Disabilities in the Zimbabwean Education System. - Mudzingwa, Nyunyutai (Advances in Social Sciences Research Journal, 2017)
Disability is about discrimination and systematic exclusion. This is aggravated in the case of women with disabilities in developing countries. Women with disabilities face attitudinal, physical and financial barriers in life. They face challenge in three broad and distinguished angles: as women in general, as people with disabilities and as women with disabilities. Therefore, being a woman with a disability is a double tragedy. This study seeks to examine the double tragedy of women with disabilities in the Zimbabwean education system. Forty-three female participants with disabilities gave their responses to the questions laid out in the questionnaire given to them in Chivi District. These participants were of different ages with different levels of education. They were given the opportunity to freely respond to the questions. The results indicated that due to marginalization and stigmatization, women with disabilities were denied access to education right from the beginning. Very few of them, went to school and managed to accomplish their goals. It is recommended that, the state and the stakeholders should empower women with disabilities in Zimbabwe. Women with disabilities should liberate themselves by revealing their potential in their communities and society at large.